Game-based futsal technical training model at academic futsal ages 15 (u-15) - Fadly Idris; Achmad Sofyan Hanif; Aan Wasan (UNIVERSITAS NEGERI JAKARTA POSTGRADUATE OF PHYSICAL EDUCATION DEPARTMENTS, 2023)
The goal of this development research is to produce a book product model of basic futsal game-based technique skills training that can provide benefits to trainers to facilitate trainers in implementing training materials. This research uses research and development model of Research and Development from Borg and Gall which consists of ten steps in research. The experimental research design is the two-group pretest-posttest design. Subjects in this study were 15 years old futsal player students consisting of 40 students with 28 items of exercise model and 40 students were not treated. Stages in this study are: preliminary research, expert evaluation, product trial consisting of small group try-out and field try group, and test product effectiveness. The model effectiveness test uses basic engineering skill tests by comparing control and experiment groups. The experimental group was performed by pre-test before the treatments and post-test after treatment. While the control group was given pre-test and post-test but not given treatment. The comparison test of control and experiment group with spss-16 then the control group is passing = 0.218, controlling = 0.684, dribbling = 0.456, shooting = 0.271 or p-value> 0.05 then there is no significant difference in the control group. While in the experimental group is passing = 0.000, controlling = 0.000, dribbling = 0.000, shooting = 0.000 or p-value <0.05 then there is a significant difference in the experimental group before and after treatment. Thus, the application of the basic technique-based futsal skill training model for the age of futsal academy needs to be done to improve the players basic engineering skills.